PENGARUH PENGGUNAAN KECERDASAN BUATAN APLIKASI CHATGPT TERHADAP PERSEPSI KUALITAS BELAJAR MAHASISWA - Br Malau, Ananda Dwi Putri; Hendripides (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of Artificial Intelligence (AI) technology has transformed various sectors, including education. One of the most influential AI-based applications today is Chat Generative Pre-trained Transformer (ChatGPT), which is widely used by students as an interactive learning assistant. This study aims to examine the influence of ChatGPT usage on students’ perceptions of learning quality. This quantitative correlational research involved 100 students selected through purposive sampling. Data were collected using an online Likert-scale questionnaire and analyzed through the Chi-Square test and Ordinal Logistic Regression. The findings reveal a significant correlation between ChatGPT usage and students’ learning quality perception. These results indicate that the more frequently and critically students use ChatGPT, the more positive their perception of learning quality becomes. ChatGPT thus serves as an innovative and adaptive learning tool that enhances educational quality when utilized responsibly and ethically.